REVERSE PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY-ULTRAVIOLET-BASED APPROACH FOR METHOD DEVELOPMENT AND VALIDATION OF LACOSAMIDE ESTIMATION IN HUMAN SERUM - MUNSHI, RENUKA; JV, VISHWAKARMA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The main aim of the study was to develop and validate a simple, accurate, and rapid isocratic reverse phase high-performance liquid chromatographic method with UV detection for the determination of lacosamide, an antiepileptic agent, in human serum. Methods: Chromatographic separation was performed using a reverse phase chromatographic column (Zorbax SB-C18, 5 μm 4.6×250 mm) with a mobile phase being a mixture of potassium dihydrogen phosphate buffer (pH adjusted to 3.0 with orthophosphoric acid) and acetonitrile (ratio of 83:17 v/v) at a flow rate of 1.2 mL/min. UV detection was carried out at 210 nm and the sample temperature was maintained at 4°C. Results: Linear calibration curves in the range of 1.012–40.894 μg/ml gave a correlation coefficient of 0.9988. The intra-day (n=6) and inter-day (n=18) precision (expressed as relative standard deviation) were in the range of 0.79–2.485% and from 0.99 to 3.21%, respectively. The retention time (in minutes) of lacosamide and internal standard was approximately 8.785±0.19 and 3.985±0.77, respectively, with no matrix interference. The method was validated for system suitability, specificity, precision, accuracy, robustness, linearity, limit of detection, and limit of quantification following the International Conference on Harmonization guidelines. The method was further validated using sera of epileptic patients consuming lacosamide, and it was observed that the results matched with the patients’ clinical response. Conclusion: Our method developed to estimate serum lacosamide level is simple, cost-effective, and reliable for therapeutic drug monitoring.